2020
DOI: 10.1002/cphc.202000018
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Beer's Law: Why the Index of Refraction Depends (Almost) Linearly on Concentration

Abstract: Beer's empiric law states that absorbance is linearly proportional to the concentration. Based on electromagnetic theory, an approximately linear dependence can only be confirmed for comparably weak oscillators. For stronger oscillators the proportionality constant, the molar attenuation coefficient, is modulated by the inverse index of refraction, which is itself a function of concentration. For comparably weak oscillators, the index of refraction function depends, like absorbance, linearly on concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…(17) one can conclude that for small variations the index of refraction is predicted to be also linearly depending on concentration. [81] This is in principle known for nearly as long as Beer's law. In contrast to the latter, the corresponding law was not formulated for the concentration, but for the density instead.…”
Section: Beyond Beer's Law -The Clausius-mosotti and The Lorentz-lorementioning
confidence: 99%
See 1 more Smart Citation
“…(17) one can conclude that for small variations the index of refraction is predicted to be also linearly depending on concentration. [81] This is in principle known for nearly as long as Beer's law. In contrast to the latter, the corresponding law was not formulated for the concentration, but for the density instead.…”
Section: Beyond Beer's Law -The Clausius-mosotti and The Lorentz-lorementioning
confidence: 99%
“…[82] We recently showed that a related law formulated for the concentration still works at resonance. [81] Interestingly, there is a law corresponding to eqn. (16), also dealing with the dependence from density instead of concentration, which is called the Newton-Laplace rule.…”
Section: Beyond Beer's Law -The Clausius-mosotti and The Lorentz-lorementioning
confidence: 99%
“…. These different expressions allow predicting [8], from tabulated values, the index of refraction, 𝑛 ! "# , of a solution of a solute 𝑆 (e.g.…”
Section: [22] An Optical Medium and Its Optical And Electromagnetic Propertiesmentioning
confidence: 99%
“…4 This means that Beer's law would be purely empiric had it not recently been derived from dispersion and electromagnetic theory. 58 The derivation was to a high degree the same as the well-known Lorentz–Lorenz relation, or, equivalently, the Clausius–Mossotti relation. 9 Those relations are also known to provide mixing rules, and therefore it seems natural to see how they are related to Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Again, it is often not realized in literature that this simplification also leads to a well-known mixing rule, which is the Gladstone–Dale rule, 12 also known as the Arago–Biot rule, 15 which we recently proved experimentally to be correct for small molar concentrations. 8…”
Section: Introductionmentioning
confidence: 99%